Effect of concomitant HIV infection on adverse drug reactions by first line antitubercular drugs - a case series analysis (Journal of Ideas in Health, 2020)
The pattern and severity of adverse drug reactions (ADRs) due to first-line anti-tubercular drugs in solely tubercular and TB-HIV co-infected patients could be different due to drug-disease and drug-drug interactions in TB-HIV co-infected patients. Nevertheless, the studies regarding this aspect are very meager. Hence a retrospective appraisal of individual case safety reports (ICSR) due to first-line antitubercular drugs spontaneously submitted to the ADR monitoring center was done for solely tubercular and TB-HIV coinfected patients. Out of eight ICSRs, four had concomitant HIV infection, and two of them were on antiretroviral (ARV) drugs. Co-infected patients showed rare and severe ADRs like optic neuritis, acute renal failure, and drug-induced liver injury (DILI). In contrast, four non-HIV co-infected tubercular patients suffered from comparatively less severe cutaneous reactions and vertigo. A high negative (-0.774) correlation coefficient between HIV co-infection and recovery status found that HIV co-infected patients had low chances of fully recovering. In conclusion, HIV co-infection and ARV drugs can affect the pattern, severity, and recovery status of adverse drug reactions due to first-line antitubercular drugs.
Keywords: Adverse Drug Reactions (ADR), TB-HIV Co-infection, First Line Antitubercular Drugs (FLD), Pharmacovigilance Programme, India